Political Marketing and Education: a study on agents, strategies and interpretations of culture - Elias Evangelista Gomes; Maria da Graça Jacintho Setton (Educação & Realidade, 2016)
The objective of this article is to reflect on political marketing as a cultural and socializational instance capable of offering political education to diverse population segments. Given their communication strategies, marketing professionals are potential producers, disseminators, mediators, and authorities on ideas relating to politics, the people and the nation of Brazil. This paper aims to examine strategies with an emphasis on mechanisms used to influence perceptions regarding social bonds between political agents, focusing primarily on candidates and voters. This article aspires to elucidate the indivisible relation between the sociology of education and the sociology of culture.